UNVEILING THE NEXT WAVE OF LEARNING: NAVIGATING CHATGPT'S IMPACTFUL APPLICATION IN EDUCATION - Jancheska, Sofija; Jancheski, Metodija (IATED, 2024)
ChatGPT, an Artificial Intelligence (AI) chatbot developed by OpenAI, has achieved an immense popularity due to its unique capabilities. Trained on a massive dataset encompassing both text and code, ChatGPT demonstrates a remarkable ability to generate code as well as creative text content. Optimized for conversations, the chatbot allows users to guide discussions and generate desired content with consecutive prompts and replies as context. Its accessibility to the general public contributed to ChatGPT becoming the fastest-growing consumer software application in history. ChatGPT possesses human-like conversational skills and a seemingly infinite knowledge. Not only it is proficient in generating answers across a multitude of subject domains, but it also excels in elaborating on responses and engaging in meaningful follow-up conversations. Leveraging its advanced natural language processing capabilities, this large language model finds applications in diverse fields, such as chatbots, virtual assistants, language translation, text summarization, question answering, personalized content generation, education, healthcare, entertainment, and customer support. The emergence of ChatGPT has inspired diverse reactions, ranging from positive to negative perspectives. Positive responses highlight its potential for advancing various fields of science and education, while negative feedback often emphasizes concerns like inaccuracies and vagueness in ChatGPT-generated content. Views on ChatGPT vary, with some seeing it as a sophisticated plagiarism tool, while others perceive it as a potential threat that could compromise artists' freedom of expression. This paper aims to explore the main advantages and disadvantages of integrating ChatGPT in education, focusing on its effective usage across diverse school subjects, encompassing natural sciences, social sciences, and formal sciences. Concrete examples will be provided to illustrate how ChatGPT can be applied in various subjects, highlighting its versatile nature. We explore the primary educational applications of ChatGPT, spanning from asking questions and acquiring information to conducting supplementary research and analyzing information sources. It is crucial to acknowledge that while ChatGPT is a valuable resource, it is not perfect, and students should not solely rely on it. Instead, we encourage students to use ChatGPT as an initial step in their research process and cross-check information from other, credible sources. Developing critical thinking about the information obtained through artificial intelligence, students need to be aware of its shortcomings and limitations. Consequently, teachers play a vital role in training students to use ChatGPT responsibly and conscientiously. Hence, we aim to unveil ways in which students and teachers can maximize the benefits of ChatGPT to achieve an exceptional learning experience.
Keywords: Artificial intelligence; ChatGPT; integration of ChatGPT in education